Face Adaptation Effects: Reviewing the Impact of Adapting Information, Time, and Transfer - Strobach, Tilo; Carbon, Claus-Christian (Frontiers in Psychology, 2013)
The ability to adapt is essential to live and survive in an ever-changing environment such as the human ecosystem. Here we review the literature on adaptation effects of face stimuli to give an overview of existing findings in this area, highlight gaps in its research literature, initiate new directions in face adaptation research and help to design future adaptation studies. Furthermore, this review should lead to better understanding of the processing characteristics as well as the mental representations of face-relevant information. The review systematises studies at a behavioral level in respect of a framework which includes 3 dimensions representing the major characteristics of studies in this field of research. These dimensions comprise (1) the specificity of adapting face information, e.g. identity, gender or age aspects of the material to be adapted to, (2) aspects of timing (e.g., the sustainability of adaptation effects), and (3) transfer relations between face images presented during adaptation and adaptation tests (e.g., images of the same or different identities). The review concludes with options for how to combine findings across different dimensions to demonstrate the relevance of our framework for future studies.